Strategi Trauma Healing Shalom Dalam Mengatasi Ketakutan Anak Pada Masa Gempa berdasarkan Lukas 24: 44-47 dan Yohannes 20: 19-23 - Pasaribu, Andar Gunawan (Jurnal Teologi Cultivation, 2022)
Trauma healing shalom (THS) is an reflection  of healing the impact of an earthquake that occurred based on Luke 24:44-47 and John 20:19-23. Trauma Healing shalom includes actions to provide relaxation, strength of faith and calm in a child's life. THS activities include singing, healing, action, learning, optimization and meetings. Trauma healing shalom aims to provide peace for children, eliminate fear and replace it with faith with the hope that God is a helper and savior. The research method is a mixture of qualitative and quantitative by using purpose sampling with community service actions. THS action was carried out on 1500 children, with a total sampling population of 125 people in the Purbatua area, Hutatinggi, Parmonangna District. This Community Service is carried out by the IAKN Tarutung academic community team in the Purbatua forest, Hutatinggi, Parmonangan District, North Tapanuli. With the trauma of shalom therapy, the child is happy, peaceful and strong, not tense and can eliminate the anxiety and fear that is in his life because of the earthquake. The method used is qualitative purpose sampling through community service actions.